Contesting Anthropocentric Masculinities Through Veganism Lived Experiences of Vegan Men - Aavik, Kadri (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores the potential of men's veganism to contest unsustainable anthropocentric masculinities. Examining what it means to be a vegan man and connections between men, masculinities and veganism addresses exploitative human-animal relations, climate change, and social inequalities as urgent and interconnected global issues. Using conceptual insights from critical studies on men and masculinities, ecofeminism, critical animal studies and vegan studies, this book examines the potential of men's veganism and vegan masculinities to foster more ethical, caring and sustainable ways of relating to nonhuman animals and to contribute towards more egalitarian gender relations. This book is grounded in a qualitative empirical study of the lived experiences of 61 vegan men in Northern Europe. The themes explored include men's transition to veganism, the emotional and embodied dimensions of men's veganism, negotiating social and intimate relationships as vegan men, and links between men's veganism, gender equality and social justice.
1. Introduction: Men, Masculinities, and the Consuming Nonhuman Animals in the Anthropocene -- 2. Going Vegan: Understanding Men's Vegan Transition Narratives -- 3. Vegan Men Making Sense of Veganism: Multiple Meanings -- 4. Beyond the Discursive: Emotions, Affects, and Embodiment in Men's Veganism -- 5. Doing Veganism and Masculinity in Everyday Interactions: Men's Strategies and Dilemmas in Communicating Veganism -- 6. Navigating Close Relationships: Vegan Men Relating to Friends, Family, and Intimate Partners -- 7. Veganism and Social Justice: Vegan Men's Gender and Intersectional Politics and Practices -- 8. Conclusions: Towards Post-anthropocentric Masculinities Through Men's Veganism.
Keywords: Men; Food science; Health; Sex; Animal welfare -- Moral and ethical aspects; Sustainability; Mens' Studies; Food Studies; Gender and Health; Animal Ethics; Gender Studies; Sustainability